Students’ Perception in Teaching Writing through Facebook Group in EFL Class - Lilies Youlia Friatin (Vision: Journal for Language and Foreign Language Learning, 2018)
This paper is a case study on teaching writing through the Facebook group in EFL class which is intended to examinethe students' perceptions on the use of the Facebook group in teaching and learning EFL writing. Descriptive qualitative by conducting closed-ended questionnaire to 17 students at the twelfth grade of SMAN 2Ciamis which were selected purposively as the respondents. The findings asserted that the students' perceptions toward the use of Facebook group in teaching and learning EFL writing showed the positive influence that the application of Facebook group gave positive effects to the students, it motivated and made the students enjoy in learning writing.